Alemtuzumab is effective against severe chronic lymphocytic leukaemia‐associated paraneoplastic pemphigus. (13th August 2013) - Bech, R.; Baumgartner‐Nielsen, J.; Peterslund, N.A.; Steiniche, T.; Deleuran, M.; d'Amore, F.
Summary Alemtuzumab (ALZ) is a monoclonal antibody used in the treatment of a variety of lymphoproliferative diseases, primarily chronic lymphocytic leukaemia (CLL). Paraneoplastic pemphigus (PNP) is a severe mucocutaneous disease, which can occur in association with B‐cell malignancies. A correct diagnosis of PNP relies on distinct clinical and histopathological features, and the demonstration, by direct immunofluorescence, of intercellular and basement membrane IgG deposits in the affected tissue. PNP is often refractory to immunosuppressive drugs and frequently has a fatal outcome. We report three cases where sustained remissions of both PNP and CLL were induced by ALZ. In one of these cases, ALZ was able to reinduce a sustained remission of PNP at the reappearance of the disorder years after the primary treatment. In all cases, the PNP diagnosis was confirmed by immunofluorescence. In conclusion, ALZ should be considered as a treatment option in severe CLL‐associated PNP. Patients should be carefully selected and receive appropriate infectious prophylaxis before, during and after ALZ treatment, due to the risk of opportunistic infections secondary to combined disease‐ and drug‐induced immunosuppression.